Household solid waste management practices and perceptions among residents in the East Coast of Malaysia - Fadhullah, Widad; Imran, Nor Ifah Najwa; Syed Ismail, Sharifah Norkhadijah; Jaafar, Mohd Hafidz; Abdullah, Hasmah (BioMed Central, 2022)
Background: Poor waste disposal practices hamper the progress towards an integrated solid waste management in households. Knowledge of current practices and perception of household solid waste management is necessary for accurate decision making in the move towards a more sustainable approach. This study investigates the household waste practices and perceptions about waste management in Panji, one of the sub-districts in Kota Bharu, Kelantan, Malaysia. Methods: A stratified random sampling technique using a cross-sectional survey questionnaire was used to collect data. A total of 338 households were interviewed in the survey and data were analyzed using SPSS. Chi-square goodness of fit test was used to determine the relationships between categorical variables, whereas Chi-square bivariate correlation test was performed to observe the correlation between the perceptions of waste segregation with socio-demographic background of the respondents. The correlation between perception of respondents with the locality, house type and waste type were also conducted. Principal component analysis was used to identify grouping of variables and to establish which factors were interrelated in any given construct. Results: The results of the study revealed that 74.3 % of households disposed of food debris as waste and 18.3% disposed of plastic materials as waste. The study also showed that 50.3% of the households segregate their waste while 49.7% did not. About 95.9% of the respondents were aware that improper waste management leads to disease; such as diarrhea and malaria. There were associations between locality, age and house type with waste segregation practices among respondents (Chi-square test, p<0.05). Principal Component Analysis showed that 17.94% of the variance has high positive loading (positive relationship) with age, marital status and, type of house. Conclusion: This study highlights the importance to design waste separation programs that suit the needs of targeted population as a boost towards sustainable solid waste management practices.